Demand analysis for time-shifted viewing in the Japanese TV market - Kasuga; Norihiro; Akihiro Nakamura; Manabu Shishikura; Toshiya Jitsuzumi; Teppei Koguchi (International Telecommunications Society (ITS), 2015)
In this study, we analyze the Japanese TV audience's preference for time-shifted viewing (TSV), which was introduced in the media market October 2015. This service has various characteristics such as a simple fee-charging video-providing service through the Internet, by which network broadcasters provide the same TV programs as on air live, without charge, and during a given time, thus relaxing time constraints. TSV is also different from a traditional terrestrial broadcasting service in the sense that TSV facilitates information exchange between the audience and the broadcasters. A similar service is already being offered in several countries including the UK, and the total usage time has increased. We empirically analyze the factors affecting an audience's TSV behavior, using the stated preference method, by studying four basic attributes: receiving equipment, existence/non-existence of commercials, necessity of registering personal information, and weeks available for viewing programs. Using conjoint analysis based on the data collected in April, 2015, we show that the coefficients of attributes for the last three attributes are all significant, which implies that the percentage of people using the TSV service would be affected by these attributes. We also find that about 20% of the viewers are willing to pay 67 yen (0.56 USD), on average, for skipping commercials. This can be considered a relatively high value, because the TV-viewing audience in Japan can enjoy most TV programs without charge.
Keywords: L82; L96; 330